Implementasi Metode Analytical Hierarchy Process (AHP) untuk Prioritas Kebutuhan Sistem Informasi Manajemen Keuangan Budidaya Ikan - Hana Syarifah Khoirunnisa (Fakultas Ilmu Komputer, 2025)
Aquaculture is one of the potential sectors in Indonesia, including small-scale fish farming businesses run by MSME players. However, many MSME fish farmers face challenges in financial management that impact the sustainability of their businesses. This research prioritizes system needs or features in developing a financial management information system. The requirement engineering approach includes requirement elicitation, requirement analysis, preparation of software requirement specification, requirement validation, and requirement. Furthermore, the Analytical Hierarchy Process (AHP) method is applied to determine the priority of features based on user-centered criteria, namely benefits, ease of use, and user needs. Data was collected from fish farming MSMEs in Jember, East Java. The results showed that 13 features were formulated and prioritized using AHP and showed that there were 8 priority orders. In conclusion, this research offers a structured needs prioritization mapping process to support the development of a user-oriented financial management system in the aquaculture sector. This research can be used as a basis for further research or system development.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: Software Requirement; Requirement Prioritization; Analytical Hierarchy Process (AHP); Financial Management System; Aquaculture